Asystole during pacemaker magnet application. Issue 10 (16th May 2017) - Ip, James E.; Liu, Todd J.; Chen, Carol L.; Lerman, Bruce B.
Abstract: Pacemaker magnet application during surgery for patients who are pacemaker‐dependent is often utilized to avoid perioperative inhibition from electromagnetic interference. We present a case during which such routine magnet use resulted in an unexpected response and discuss the limitations and nuances of this common practice.